Complex-phase ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

By regulating the composition of the positive electrode material of sodium ferric pyrophosphate, forming a composite phase structure with heterojunction, the problem of high raw material cost in the prior art is solved, and a high conductivity, excellent rate performance and low cost positive electrode material preparation is achieved.

CN119812290AActive Publication Date: 2025-04-11NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202510300223.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

In the prior art, when transition metal doping and carbon coating composite synergistically improve the electrochemical performance of sodium ferro pyrophosphate positive electrode material, it is easy to increase the cost of raw materials, limiting the large-scale production and commercial application of materials.

Method used

Through inherent component regulation, a complex phase sodium ferric pyrophosphate positive electrode material with xNa4Fe3(PO4)2(P2O7)·(1-x)Na3.12Fe2.44(P2O7)2/C chemical formula was prepared, and a built-in electric field was formed using a heterojunction of the two phases to increase the conductivity and reduce the generation of the inactive phase NaFePO4.

Benefits of technology

It achieves the improvement of the conductivity and energy density of the positive electrode material, improves the rate performance, and reduces the generation of inactive phases, avoids the use of transition metal doping, and is low in cost and simple in preparation, which is suitable for large-scale production and commercial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812290A_ABST
    Figure CN119812290A_ABST
Patent Text Reader

Abstract

The invention discloses a multiphase ferric sodium pyrophosphate positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of positive electrode materials. The complex-phase phosphoric acid and sodium ferric pyrophosphate positive electrode material has the following chemical formula: xNa4Fe3 (PO4) 2 (P2O7). (1-x) Na3. 12Fe2. 44 (P2O7) 2 / C, C is a carbon coating layer, and the content of the C is 8-10 wt% of the total mass of the composite-phase phosphoric acid and sodium ferric pyrophosphate positive electrode material; xNa4Fe3 (PO4) 2 (P2O7). (1-x) Na3.12Fe2.44 (P2O7) 2 is a core layer, and x is greater than or equal to 0.76 and less than or equal to 0.88. Under the condition that transition metal elements are not added for doping, the electrochemical performance of the complex-phase ferric sodium phosphate pyrophosphate positive electrode material can be obviously improved by regulating and controlling the ratio of positive ions to negative ions of original components of ferric sodium phosphate pyrophosphate, and the complex-phase ferric sodium phosphate pyrophosphate positive electrode material is low in cost, simple to prepare and suitable for large-scale production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of iron-based phosphate positive electrode materials, and in particular relates to a composite sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium iron pyrophosphate [Na4Fe3(PO4)2(P2O7)] cathode material has become the research focus of iron-based phosphate cathode materials for sodium ion batteries due to its advantages such as high theoretical capacity, good air stability and excellent cycle performance. However, the intrinsic conductivity of sodium iron pyrophosphate is low, and it is easy to generate inactive phase NaFePO4 during material synthesis, which makes it difficult to fully utilize the theoretical capacity in practical applications. Therefore, how to reduce the generation of NaFePO4 in sodium iron pyrophosphate cathode materials and improve the intrinsic conductivity of the material has become a research focus.

[0003] At present, the related technologies disclose that the electrochemical performance of sodium iron pyrophosphate can be improved by composition regulation, transition metal doping and carbon coating composite. Among them, the synergistic strategy of transition metal doping and carbon coating composite is one of the most effective measures. For example, Tao et al. used mechanically assisted synthesis of Na4Fe 2.9 Mn 0.1 (PO4)2P2O7@C composite material achieved better electrochemical performance.

[0004] However, the synergistic strategy of transition metal doping and carbon coating composite is still insufficient. For example, the introduction of transition metal doping can easily increase the cost of raw materials and limit large-scale production and commercial applications. Summary of the invention

[0005] The present application discloses a composite sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof, aiming to solve the technical problem of easily increasing raw material costs in the composite synergistic improvement of transition metal doping and carbon coating.

[0006] In order to achieve the above objectives, the technical solution adopted in this application is:

[0007] In a first aspect, the present application provides a composite sodium iron phosphate pyrophosphate positive electrode material having a chemical formula (1):

[0008] xNa4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Fe 2.44 (P2O7)2 / C (1);

[0009] Among them, C is a carbon coating layer, and its content is 8-10wt% of the total mass;

[0010] xNa4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Fe 2.44 (P2O7)2 is the core layer, 0.72 ≤x ≤0.88.

[0011] In a possible implementation manner, the value of x in formula (1) is 0.84-0.88.

[0012] In a second aspect, the present application also provides a method for preparing the composite sodium iron phosphate pyrophosphate positive electrode material as described above, the steps comprising:

[0013] Providing a precursor powder containing a sodium source, an iron source, a phosphorus source and a carbon source, wherein the molar ratio of Na, Fe and P in the precursor powder is (0.9-1):(0.7-0.75):1;

[0014] The precursor is calcined at a temperature of 400-650° C. in a non-oxidizing atmosphere to obtain the composite phosphate sodium iron pyrophosphate positive electrode material.

[0015] In a possible implementation manner, the sodium source is at least one of sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium hydrogen phosphate, and sodium pyrophosphate.

[0016] In a possible implementation, the iron source is at least one of ferric nitrate, ferric sulfate, ferric chloride, ferroferric oxide, ferrous oxide, ferrous oxide, ferrous oxalate, ferric phosphate, and ferric pyrophosphate.

[0017] In a possible implementation, the phosphorus source is at least one of phosphoric acid, pyrophosphoric acid, sodium phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, triammonium phosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.

[0018] In a possible implementation, the carbon source is at least one of oxalic acid, citric acid, soluble starch, sucrose and glucose.

[0019] In a possible implementation manner, during the calcination, the heating rate is 1-5°C / min and the time is 10-25h.

[0020] In a third aspect, the present application also provides a sodium ion battery positive electrode, which comprises the composite sodium iron phosphate pyrophosphate positive electrode material described in the above application.

[0021] In a fourth aspect, the present application also provides a sodium ion battery, which comprises the sodium ion battery positive electrode described in the above application.

[0022] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0023] The composite sodium iron phosphate pyrophosphate cathode material disclosed in the present application is regulated by inherent components and has a chemical formula of xNa4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Fe 2.44 The (P2O7)2 / C heterojunction, on the one hand, can form a built-in electric field through the two-phase interface heterojunction, thereby improving the conductivity of the prepared positive electrode material; on the other hand, it can reduce the energy barrier for sodium ion migration, thereby promoting the reversible sodium ion kinetics, so that the positive electrode material has higher energy density and rate performance; thirdly, it can effectively reduce the generation of inactive phase NaFePO4, reduce the hindrance of inactive phase to sodium ion migration, and fully exert the electrochemical properties of the positive electrode material; fourthly, it can improve the electrochemical properties of sodium iron pyrophosphate positive electrode materials while avoiding the introduction of transition metal elements, which is low-cost and simple to prepare, and is suitable for large-scale production and commercial use. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 provided in this application;

[0026] Figure 2 XRD patterns of the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 provided in this application;

[0027] Figure 3 XRD patterns of the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 provided in the present application at 8 to 50° and 9 to 11°, respectively;

[0028] Figure 4 This is a rate test diagram of the button battery provided in this application in the voltage range of 1.7~4.3V;

[0029] Figure 5 This is a charge and discharge curve diagram of the button battery provided in this application at 0.1 C. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] In the following description of this specification, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural.

[0032] In the following description of this specification, the term "at least one" refers to one or more; "plurality" refers to two or more. "At least one of the following" or similar descriptions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" means one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0033] In the following description of this specification, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0034] In the following description of this specification, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any stated value or intermediate value in the stated range and any other stated value or intermediate value in the stated range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.

[0035] Unless otherwise specified, the technical / scientific terms used in this specification have the same meanings as those generally understood by those skilled in the art. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0036] Before explaining the invention in detail with reference to the embodiments, the present invention will be described in detail.

[0037] Sodium iron pyrophosphate [Na4Fe3(PO4)2(P2O7)] is one of the commonly used iron-based phosphate positive electrodes for sodium ion batteries, but its intrinsic conductivity is poor and it is easy to generate inactive impurity phase NaFePO4, which limits the actual electrochemical performance of sodium iron pyrophosphate. In response to this problem, the inventors found that when the ratio of the raw material (Na+P):Fe is close to 1:1, due to the influence of thermodynamic factors during the preparation process, it is easy to inevitably produce inactive impurity phase NaFePO4 at the synthesis temperature. Therefore, optimizing and regulating the composition ratio of the raw materials Na, Fe and P elements, that is, increasing the proportion of Na and P, is expected to inhibit the formation of inactive impurity phase NaFePO4 and achieve the effect of improving the purity of the material. In view of this, the inventors unexpectedly discovered during in-depth research that adding excess Na and P elements to the material synthesis can derive Na in situ. 3.12 Fe 2.44 (P2O7)2 active phase and form xNa4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Fe 2.44 (P2O7)2 / C positive electrode material, the heterojunction at the interface between the two phases can form a built-in electric field that can enhance the electronic conductivity, which is beneficial to improving the conductivity of Na4Fe3(PO4)2(P2O7), so that the prepared composite sodium iron phosphate pyrophosphate positive electrode material has higher electrochemical performance.

[0038] Example 1

[0039] This embodiment provides a preparation method for a composite sodium iron phosphate pyrophosphate positive electrode material, the chemical formula of which is 0.76Na4Fe3(PO4)2(P2O7)·0.24Na 3.12 Fe 2.44 (P2O7)2 / C, wherein the carbon content is 8.28% of the total mass, and the specific preparation process includes:

[0040] Step 1: 2.9520 g of sodium dihydrogen phosphate, 7.5144 g of ferric nitrate nonahydrate, 0.1494 g of ammonium dihydrogen phosphate and 30 wt% of citric acid were dissolved in deionized water and stirred evenly, and the resulting solution was spray dried in a spray dryer at an inlet air temperature of 165° C. and an outlet air temperature of 90° C. to obtain a precursor powder;

[0041] Step 2: Place the precursor powder in an Ar / H2 mixed atmosphere (volume ratio of 95:5), heat it to 300°C at a rate of 2°C / min and keep it warm for 3 hours, and heat it to 550°C at a rate of 2°C / min and keep it warm for 10 hours, and cool it to room temperature in the furnace to obtain the composite phosphate sodium iron pyrophosphate positive electrode material.

[0042] Example 2

[0043] This embodiment provides a preparation method for a composite sodium iron phosphate pyrophosphate positive electrode material, the chemical formula of which is 0.88Na4Fe3(PO4)2(P2O7)·0.12Na 3.12 Fe 2.44 (P2O7)2 / C, wherein the carbon content is 8.06% of the total mass, and the specific preparation process includes:

[0044] Step 1: 2.6758 g of sodium dihydrogen phosphate, 6.7872 g of ferric nitrate nonahydrate, 0.0871 g of ammonium dihydrogen phosphate and 30 wt% of citric acid were dissolved in deionized water and stirred evenly, and the resulting solution was spray dried in a spray dryer at an inlet air temperature of 165°C and an outlet air temperature of 90°C to obtain a precursor powder;

[0045] Step 2: Place the precursor powder in an Ar / H2 mixed atmosphere (volume ratio of 95:5), heat it to 300°C at a rate of 2°C / min and keep it warm for 3 hours, and heat it to 550°C at a rate of 2°C / min and keep it warm for 10 hours, and cool it to room temperature in the furnace to obtain the composite phosphate sodium iron pyrophosphate positive electrode material.

[0046] Example 3

[0047] This embodiment provides a preparation method for a composite sodium iron phosphate pyrophosphate positive electrode material, the chemical formula of which is 0.84Na4Fe3(PO4)2(P2O7)·0.16Na 3.12 Fe 2.44 (P2O7)2 / C, wherein the carbon content is 8.24% of the total mass, and the specific preparation process includes:

[0048] Step 1: 2.7678 g of sodium dihydrogen phosphate, 7.0296 g of ferric nitrate nonahydrate, 0.996 g of ammonium dihydrogen phosphate and 30 wt% of citric acid were dissolved in deionized water and stirred evenly, and the resulting solution was spray dried in a spray dryer at an inlet air temperature of 165° C. and an outlet air temperature of 100° C. to obtain a precursor powder;

[0049] Step 2: Place the precursor powder in an Ar / H2 mixed atmosphere (volume ratio of 95:5), heat it to 300°C at a rate of 2°C / min and keep it warm for 3 hours, and heat it to 550°C at a rate of 2°C / min and keep it warm for 10 hours, and cool it to room temperature in the furnace to obtain the composite phosphate sodium iron pyrophosphate positive electrode material.

[0050] In order to illustrate the phase composition and electrochemical properties of the composite sodium iron phosphate pyrophosphate positive electrode material prepared in Examples 1-3 of the present application, the present application also provides Comparative Examples 1-3, and analyzes and explains them in combination with the Examples and Comparative Examples.

[0051] Comparative Example 1

[0052] This comparative example provides a preparation of a sodium iron phosphate pyrophosphate positive electrode material, the chemical formula of which is Na4Fe3(PO4)2(P2O7) / C, and the carbon content is 7.78% of the total mass. The specific preparation process includes:

[0053] Step 1: 2.3996 g of sodium dihydrogen phosphate, 6.0600 g of ferric nitrate nonahydrate and 30 wt% of citric acid were dissolved in deionized water and stirred evenly, and the resulting solution was spray dried in a spray dryer at an inlet air temperature of 165° C. and an outlet air temperature of 90° C. to obtain a precursor powder;

[0054] Step 2: Place the precursor powder in an Ar / H2 mixed atmosphere (volume ratio of 95:5), heat it to 300°C at a rate of 2°C / min and keep it warm for 3 hours, and heat it to 550°C at a rate of 2°C / min and keep it warm for 10 hours, and cool it to room temperature in the furnace to obtain the sodium iron pyrophosphate positive electrode material.

[0055] Comparative Example 2

[0056] This comparative example provides a preparation method for a sodium iron pyrophosphate positive electrode material, the chemical formula of which is Na2FeP2O7 / C, and the carbon content is 7.78% of the total mass. The specific preparation process includes:

[0057] Step 1: 2.3996 g of sodium dihydrogen phosphate, 4.04 g of ferric nitrate nonahydrate and 30 wt% of citric acid were dissolved in deionized water and stirred evenly, and the resulting solution was spray dried by a spray dryer at an inlet air temperature of 165° C. and an outlet air temperature of 90° C. to obtain a precursor powder;

[0058] Step 2: Place the precursor powder in an Ar / H2 mixed atmosphere (volume ratio of 95:5), heat it to 300°C at a rate of 2°C / min and keep it warm for 3 hours, and heat it to 550°C at a rate of 2°C / min and keep it warm for 10 hours, and cool it to room temperature in the furnace to obtain the sodium iron pyrophosphate positive electrode material.

[0059] Comparative Example 3

[0060] This comparative example provides a preparation method of a sodium iron pyrophosphate positive electrode material, the chemical formula of which is Na 3.12 Fe 2.44 (P2O7)2 / C, with a carbon content of 8.44% of the total mass, the specific preparation process includes:

[0061] Step 1: 3.7434 g of sodium dihydrogen phosphate, 9.8576 g of ferric nitrate nonahydrate, 1.0123 g of ammonium dihydrogen phosphate and 30 wt% of citric acid were dissolved in deionized water and stirred evenly, and the resulting solution was spray dried by a spray dryer at an inlet air temperature of 165° C. and an outlet air temperature of 90° C. to obtain a precursor powder;

[0062] Step 2: Place the precursor powder in an Ar / H2 mixed atmosphere (volume ratio of 95:5), heat it to 300°C at a rate of 2°C / min and keep it warm for 3 hours, and heat it to 550°C at a rate of 2°C / min and keep it warm for 10 hours, and cool it to room temperature in the furnace to obtain the sodium iron pyrophosphate positive electrode material.

[0063] Test Example 1

[0064] The present application conducted SEM characterization on the composite sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1, and the results were Figure 1 As shown. Among them, Figure 1 This is the SEM image of the positive electrode material prepared in Example 1.

[0065] according to Figure 1 It can be seen that the composite sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 above is a spherical structure, and the surface is coated with a carbon coating layer.

[0066] Test Example 2

[0067] In order to illustrate the structural composition of the positive electrode materials prepared in the examples of the present application, the present application conducted XRD characterization on the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, and the results were as follows: Figure 2-3 As shown. Among them, Figure 2 XRD patterns of the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3; Figure 3 a in the figure is the XRD pattern of the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 at 8 to 50°; Figure 3 b is the XRD pattern of the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 at 9 to 11°.

[0068] according to Figures 2 to 3 It can be seen that Comparative Example 3 synthesized Na with good crystallinity. 3.12 Fe 2.44 (P2O7)2 / C; while in Examples 1 to 3, while preparing the synthetic Na4Fe3(PO4)2(P2O7) main phase, Na 3.12 Fe 2.44 The diffraction peak of the (P2O7)2 second phase can be considered that Examples 1 to 3 have successfully synthesized a Na4Fe3(PO4)2(P2O7) main phase and Na 3.12 Fe2.44 (P2O7)2 second phase heterojunction type composite phase sodium iron phosphate pyrophosphate positive electrode material, and all have good crystallinity. Specifically:

[0069] (1) Example 1 successfully prepared 0.76 Na4Fe3(PO4)2(P2O7)·0.24Na 3.12 Fe 2.44 (P2O7)2 / C;

[0070] (2) Example 2 successfully prepared 0.88 Na4Fe3(PO4)2(P2O7)·0.12Na 3.12 Fe 2.44 (P2O7)2 / C;

[0071] (3) Example 3 successfully prepared 0.84 Na4Fe3(PO4)2(P2O7)·0.16Na 3.12 Fe 2.44 (P2O7)2 / C.

[0072] In order to illustrate the electrochemical performance of the composite sodium iron phosphate pyrophosphate positive electrode material prepared in Examples 1 to 3 of the present application, the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are made into positive electrode sheets and used for the assembly of sodium ion batteries, specifically comprising:

[0073] Step 1: The positive electrode materials prepared in the embodiment and the comparative example are respectively mixed with conductive carbon black and a binder in a mass ratio of 8:1:1, and an organic solvent N-methylpyrrolidone is added and mixed thoroughly to form a slurry. A 50 μm scraper is used to evenly coat the slurry on an aluminum foil, and the slurry is dried and cut into discs with a diameter of 12 mm to obtain positive electrode sheets.

[0074] Step 2: Each positive electrode sheet is used as the positive electrode of the battery, the sodium sheet is used as the counter electrode, the electrolyte is 1M sodium perchlorate dissolved in a solvent with a volume ratio of propylene carbonate to ethylene carbonate of 1:1, and 5% of the total volume fraction of fluoroethylene carbonate is added, and glass fiber is used as a separator to assemble a sodium ion button cell, and the obtained button cell is subjected to electrochemical testing, and the results are as follows: Figures 4 to 5 As shown. Among them, Figure 4 This is the rate test diagram of button batteries in the voltage range of 1.7~4.3V; Figure 5 This is the charge and discharge curve of the button battery at 0.1 C.

[0075] according to Figure 4It can be seen that the positive electrode materials prepared in Examples 1 to 3 of the present application have better rate performance and improved specific capacity than those in Comparative Examples 1 to 3. Specifically, the first cycle specific capacity of the button cell assembled with the composite sodium iron phosphate pyrophosphate positive electrode materials prepared in Examples 1 to 3 at 0.1C is 90.6 mAh·g -1 、96.4mAh·g -1 、106.4mAh·g -1 , which is higher than 76.4 mAh·g in Comparative Example 1 -1 , 74.3 mAh·g in Comparative Example 2 -1 and 75.3 mAh·g in Comparative Example 3 -1 Therefore, the present invention adds excessive Na and P elements during the calcination process to in-situ derive Na 3.12 Fe 2.44 (P2O7)2 active phase and form x Na4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Fe 2.44 (P2O7)2 / C can effectively improve the rate performance of sodium iron pyrophosphate positive electrode materials.

[0076] according to Figure 5 It can be seen that the second phase Na 3.12 Fe 2.44 The introduction of (P2O7)2 has good electrochemical performance while maintaining the original higher charge and discharge voltage platform.

[0077] In addition, this application also explores the second phase Na 3.12 Fe 2.44 The influence of the proportion of (P2O7)2 on the electrochemical performance of the composite sodium iron pyrophosphate positive electrode material is as follows:

[0078] Table 1: Electrochemical performance test results of composite cathode materials with different proportions of the second phase

[0079]

[0080] According to Table 1, the composite sodium iron phosphate pyrophosphate positive electrode material provided by the present application has a high discharge specific capacity and excellent cycle stability, especially when x is 0.84, it exhibits the most excellent electrochemical performance. The reason for this phenomenon may be that the present application generates a heterojunction at the interface of the two phases through targeted ratio regulation, thereby improving the material conductivity and sodium ion diffusion coefficient, and improving the specific capacity and cycle performance. At the same time, it can be seen from the table that when the proportion of the introduced second phase is relatively small, the performance improvement is limited, and the improvement effect is difficult to play; when the proportion of the introduced second phase is too large, the specific capacity of the overall material is close to the second phase with a smaller theoretical capacity, resulting in a decrease in the specific capacity, and it is easy to generate large internal stress at the interface of the two phases during the charge and discharge process, destroying the structural integrity of the material, and thus affecting the cycle performance.

[0081] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0082] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A composite sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The chemical formula having formula (1) is: xNa4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Feb 2.44 (P2O7)2 / C (1); Among them, C is a carbon coating layer, and its content is 8-10wt% of the total mass; xNa4Fe3(PO4)2(P2O7)·(1-x)Na 3.12 Fe 2.44 (P2O7)2 is the core layer, 0.72≤x ≤0.

88.

2. The composite sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The value of x in formula (1) is 0.84~0.

88.

3. A method for preparing the composite sodium iron pyrophosphate positive electrode material according to claim 1 or 2, characterized in that: Contains steps: Providing a precursor powder containing a sodium source, an iron source, a phosphorus source and a carbon source, wherein the molar ratio of Na, Fe and P in the precursor powder is (0.9-1):(0.7-0.75):1; The precursor is calcined at a temperature of 400-650° C. in a non-oxidizing atmosphere to obtain the composite sodium iron phosphate pyrophosphate positive electrode material.

4. The preparation method according to claim 3, characterized in that: The sodium source is at least one of sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium hydrogen phosphate, and sodium pyrophosphate.

5. The preparation method according to claim 3, characterized in that: The iron source is at least one of ferric nitrate, ferric sulfate, ferric chloride, ferroferric oxide, ferrous oxide, ferrous oxide, ferrous oxalate, ferric phosphate, and ferric pyrophosphate.

6. The preparation method according to claim 3, characterized in that: The phosphorus source is at least one of triammonium phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, pyrophosphoric acid, sodium phosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.

7. The preparation method according to claim 3, characterized in that: The carbon source is at least one of oxalic acid, citric acid, soluble starch, sucrose and glucose.

8. The preparation method according to claim 3, characterized in that: During the calcination, the heating rate is 1-5°C / min and the time is 10-25 h.

9. A sodium ion battery positive electrode, characterized in that: The invention comprises the composite sodium iron phosphate pyrophosphate positive electrode material according to claim 1 or the composite sodium iron phosphate pyrophosphate positive electrode material prepared by any one of the methods according to claims 3 to 8.

10. A sodium ion battery, characterized in that: A sodium ion battery positive electrode comprising the positive electrode of claim 9.

Citation Information

Patent Citations

  • Preparation method and application of titanium-doped carbon-coated ferric sodium pyrophosphate material

    CN116750741A

  • Preparation method of single crystal type sodium ion battery positive electrode material sodium ferric pyrophosphate

    CN117228646A

  • Method for synthesizing ferric sodium pyrophosphate positive electrode material by using ferric phosphate

    CN118062820A

  • Sodium ferric phosphate pyrophosphate / C composite material as well as preparation method and application thereof

    CN118117065A

  • Preparation of ferric sodium pyrophosphate / rGO composite material with heterogeneous symbiotic structure and application of ferric sodium pyrophosphate / rGO composite material in sodium ion battery

    CN119181800A

Cited By

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and sodium ion battery

    CN121565860A

  • A sodium iron pyrophosphate cathode material and its preparation method, and its application in sodium-ion batteries.

    CN121565860B

  • Sodium-ion battery monomer, preparation method thereof, battery device and power utilization device

    CN121583993A